2022
DOI: 10.1097/mpg.0000000000003386
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of High‐dose Cholecalciferol in Patients With Inflammatory Bowel Disease Receiving Infliximab

Abstract: Objective:Vitamin D deficiency is prevalent in patients with inflammatory bowel disease (IBD). The goal of this study was to assess the efficacy and safety of high-dose, interval cholecalciferol administration in patients with IBD receiving infliximab.Methods:This prospective, longitudinal, open-label study enrolled pediatric and young adult patients with IBD and vitamin D deficiency. Subjects received 50,000 IU every 4 to 5 weeks (n = 11) or 100,000 IU every 6 to 8 weeks (n = 32) of oral cholecalciferol for 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
1
0
1
Order By: Relevance
“…Autoři se domnívají, že pacienti s IBD budou zřejmě vyžadovat vyšší dávkování vitaminem D než běžná populace. (31) S přibývajícími studiemi zabývajícími se efektem substituce vitaminu D na průběh IBD množství odlišných závěrů bohužel narůstá. Loňská velká metaanalýza hodnotící 22 randomizovaných klinických studií, která zahrnula 1874 jedinců, neprokázala, že by substituce vitaminem D ovlivňovala klinickou odpověď pacientů na léčbu IBD nebo riziko relapsu onemocnění.…”
Section: Vztah Vitaminu D K Aktivitě Ibdunclassified
“…Autoři se domnívají, že pacienti s IBD budou zřejmě vyžadovat vyšší dávkování vitaminem D než běžná populace. (31) S přibývajícími studiemi zabývajícími se efektem substituce vitaminu D na průběh IBD množství odlišných závěrů bohužel narůstá. Loňská velká metaanalýza hodnotící 22 randomizovaných klinických studií, která zahrnula 1874 jedinců, neprokázala, že by substituce vitaminem D ovlivňovala klinickou odpověď pacientů na léčbu IBD nebo riziko relapsu onemocnění.…”
Section: Vztah Vitaminu D K Aktivitě Ibdunclassified
“…Indeed, previous studies have shown that low vitamin D levels are associated with disease severity and vedolizumab failure in patients with IBD [13][14][15]. Additionally, despite high doses of vitamin D, patients can achieve sufficiency even with supplementation [16,17]. We previously described, in a small group of patients, a lack of clinical remission when vitamin D levels are less than 30 ng/mL and persistent elevation in C-reactive protein (CRP) when vitamin D levels are extremely low (<15 ng/mL) [18].…”
Section: Introductionmentioning
confidence: 99%